Os precedentes judiciais como fundamento para a concessão da tutela da evidência. - Guedes, Lorena Braga D'Almeida (2018)
The contribution of legal hermeneutics to the evolution of norm theory is remarkable, especially in the sphere of procedural law. As a consequence of the rich doctrinal production on this subject, stands out: 1) the sedimentation of the distinction between text and norm, projecting a new paradigm also on the theory of the sources of law; 2) the understanding that the activity of applying law is inseparable from interpretation, which culminated in conferring / recognizing to judging activity the power to also act creatively in the realization of law. A new perspective was opened on the jurisdictional action, and, at this point, is possible to verify that Brazilian civil procedural law has been increasingly receptive to institutes that traditionally belongs to common law. As an example, the development of the respecting precedents - consolidated in English Law and US Law - in Brazil is received with special concern in combining legal certainty and equality with celerity, incorporating peculiarities not seen in Anglo-Saxon scope. With this purpose, doctrine and law enforcers raise the problem of the identification of a system of precedents that meets the peculiarities of the legal model adopted in Brazil. At the same time, the Brazilian procedural law has sought to make jurisdictional effectiveness feasible, since the reforms to CPC/73, having as the main objective the realization of the rights that have been recognized in the sphere of the Judiciary. In this ambit, Brazilian law incorporated innovations that even reached the elaboration of a new legal document - the CPC/15. Among the mechanisms proposed by the legislator are anticipatory techniques and differentiated tutelages, with special emphasis on temporary protection of urgency and of evidence, included in Livro V of CPC/15, from art. 294 until the art. 311. Taking these considerations in view, this study has as object of study the systematization of respect for judicial precedents and their correlation with the hypothesis of applying the protection of evidence based on binding precedents, having as dogmatic basis the art. 311, II, CPC/15. The central relevance of the work can be verify in the fact that such a device authorizes the granting of the summary procedure analyzed only on the basis of a thesis established in the trial of repetitive cases or in a binding summary. As a result, the exclusion of the hypothesis of protection of evidence based on the binding precedents established in the mold of art. 927, also from CPC/15. The problem to be faced is: it is possible to apply the protection of the evidence based on the binding precedents formulated according to art. 927 CPC/15? It is a question of departure whose answer was developed using the hypothetical-deductive method, based on theoretical premises raised in the first chapter. Thus, this work includes an analysis on the systematization of respect for precedents and on the legal regime of the protection of evidence. The suggested topic is relevant, since it intends to contribute to the maturation of the new systematic proposal to Brazilian proceduralism with the advent of CPC/15.